IMPLIKASI P5 DALAM PENGUATAN KOMPETENSI 6C PADA GURU SEKOLAH TK BINA UKHWAH KABUPATEN PIDIE - Basri, Novysa; Syahrin, Alfi; Sharfina; Halim, Fauziatul; Saputra, Rudy Juli; Aryesha, Vinny (LPPM Universitas Al Muslim, 2023)
This community service activity aimed to create competent teachers in their fields and keeping up with current developments in 6C-based education towards the 21st century. Current learning materials do not focus on mastery of the material but teachers must be able to provide value and character education. This is a current obstacle for teachers, so it is necessary for teachers to understand P5 in strengthening 6C competencies. This community service activity was carried out at Bina Ukhwah Pidie Kindergarten. The method of implementing activities was by providing knowledge of the implications of P5 in strengthening 6C competencies to Bina Ukhwah Kindergarten teachers to make teachers creative, innovative and follow independent learning. The stages of implementing activities were in the form of preparation, implementation and evaluation stages. The results of the implementation of the activities showed that teachers' understanding, creativity and innovation in the field of education in 6C are very important for learning in classes following P5. This community service activity can develop new theories and provide alternative problem solving solutions related to current educational issues, because it is a problem of lacking teacher competence and teachers being unable to realize 21st century learning. In the future, it is hoped that teachers will have the ability to strengthen the 6C competencies in order to create an environment learning based on Pancasila as well as active, creative and innovative learning.